Close-range photogrammetry for 3D rock joint roughness evaluation - Paixão, A.; Muralha, J.; Resende, R.; Fortunato, E. (Rock Mechanics and Rock Engineering, 2022)
Photogrammetry-based methods have been gaining importance in roughness evaluation of rock joints as an alternative to traditional approaches. However, the influence of some aspects is still unclear, such as the number and orientation of camera poses, the parameters of Structure-from-Motion and meshing algorithms, the resolution, and the accuracy of the reconstructed models. To fill this gap, 3D models of a rock joint specimen obtained by photogrammetry, generated using different settings, are compared with a reference model obtained by contact digitalization. The results suggest that comparable results can be achieved if equivalent vertex densities are attained and the photos adequately cover the specimen. Percentiles p5 and p95 of surface deviations were generally <0.1 mm. Estimated roughness parameters showed reduced variability, with minor impact in shear strength evaluations. DSLR or smartphones may be used with this method, which is far more accessible, faster to implement, less expensive than most currently available approaches.